Moral hazard in a mutual health-insurance system: German Knappschaften, 1867-1914 - Timothy Guinnane; Jochen Streb (Yale University, Economic Growth Center, 2009)
This paper studies moral hazard in a sickness-insurance fund that provided the model for socialinsurance schemes around the world. The German Knappschaften were formed in the medieval period to provide sickness, accident, and death benefits for miners. By the mid-nineteenth century, participation in the Knappschaft was compulsory for workers in mines and related occupations, and the range and generosity of benefits had expanded considerably. Each Knappschaft was locally controlled and self-funded, and their admirers saw in them the ability to use local knowledge and good incentives to deliver benefits at low costs. The Knappschaft underlies Bismarck's sickness and accident insurance legislation (1883 and 1884), which in turn forms the basis of the German social-insurance system today and, indirectly, many social-insurance systems around the world. This paper focuses on a problem central to any insurance system, and one that plagued the Knappschaften as they grew larger in the later nineteenth century: the problem of moral hazard. Replacement pay for sick miners made it attractive, on the margin, for miners to invent or exaggerate conditions that made it impossible for them to work. Here we outline the moral hazard problem the Knappschaften faced as well as the internal mechanisms they devised to control it. We then use econometric models to demonstrate that those mechanisms were t best imperfect.
Keywords: N33; N43; H55; H53; I18; 330; sickness insurance; moral hazard; Knappschaft; social insurance; Gesetzliche Krankenversicherung; Sozialversicherung; Moral Hazard; Bergbauberufe; Wirtschaftsgeschichte; Deutschland (bis 1945)